Combined resistance and aerobic training improves lung function and mechanics and fibrotic biomarkers in overweight and obese women - Silva-Reis, Anamei; Rodrigues Brandao-Rangel, Maysa Alves; Moraes-Ferreira, Renilson; Gonçalves-Alves, Thiago Gibson; Souza-Palmeira, Victor Hugo; Aquino-Santos, Helida Cristina; Bachi, Andre Luis Lacerda; Oliveira, Luis Vicente Franco de; Lopes-Martins, Rodrigo Álvaro Brandão; Oliveira-Silva, Iranse; Albertini, Regiane; Frison, Claudio Ricardo; et al. (Frontiers in Physiology, 2022)
BACKGROUND: Obesity impairs lung function and mechanics and lead to low-grade inflammation, but the effects of combined physical exercise (CPE) on that are unknown. METHODS: We investigated the effects of 12 weeks of CPE (aerobic + resistance training), in non-obese (n=12), overweight (n=17) and obese grade I (n=11) women. Lung function and lung mechanics was evaluated. The systemic immune response was evaluated by the whole blood analysis and biomarkers measurements, while the pulmonary fibrotic biomarkers were evaluated in the breath condensate. RESULTS: CPE improved (forced vital capacity) FVC% (p<0.001) and (peak expiratory flow) PEF% (p<0.0003) in obese group, the resistance of respiratory system (R5Hz) in non-obese (p<0.0099), overweight (p<0.0005) and obese (p<0.0001) groups; resistance of proximal airways (R20Hz) in non-obese (p<0.01), overweight (p<0.0009) and obese (p<0.0001) groups; resistance of distal airways (R5Hz-R20Hz) in non-obese (p<0.01), overweight (p<0.0012) and obese (p<0.0001) groups; reactance of the respiratory system (X5Hz) in non-obese (p<0.01), overweight (p<0.0006) and obese (p<0.0005) groups; impedance of respiratory system (Z5Hz) in non-obese (p<0.0099), overweight (p<0.0005) and obese (p<0.0001) groups; central resistance (RCentral) in non-obese (p<0.01), overweight (p<0.001) and obese (p<0.0003) groups; and in the peripheral resistance (RPeripheral) in non-obese (p<0.03), overweight (p<0.001) and obese (p<0.0002) groups. CPE reduced the pro-fibrotic IGF-1 levels in BC in overweight (p<0.0094) and obese (p<0.0001) and increased anti-fibrotic Klotho levels in BC in obese (p<0.0001) groups, reduced levels of exhaled nitric oxide in overweight (p<0.03) and obese (p<0.0001) groups. CONCLUSIONS: CPE improves lung function, mechanics, and pulmonary immune response in overweight and obese grade I women by increasing anti-fibrotic protein Klotho and reducing pro-fibrotic IGF-1.